The Effect of Impairment Losses on the Firm Value of Conventional Banking Companies Listed on the Indonesian Stock Exchange 2022-2023 - Nisa, Rohadatun; Yadiati, Winwin; Yunita, Devianti (International Journal of Science and Society, 2025)
Allowance for Impairment Losses (CKPN) is a predetermined amount that banks set aside in order to prepare for the possibility of failure. According to PSAK 71, the method of computation for CKPN has switched from the incurred loss model to the predicted credit loss approach. This change represents a significant change. It is the existence of certain rules regarding the calculation of CKPN that has an effect on the market value of the company. The purpose of this research is to investigate the impact that Allowance for Impairment Losses has on the value of a company. The Bank Group Based on Core Capital (KBMI) and Profitability, the latter of which is defined via Net Interest Margin, are the control variables that are used in this research. For the purpose of this research, 74 conventional banking businesses that were continually listed on the Indonesia Stock Exchange over the period of 2022-2023 are the subjects of investigation. A basic random sampling method was used to collect the sample, which consisted of a total of 37 separate businesses that were included in the investigation. In all, the observation period lasted for a period of two different years. The hypothesis was put to the test via the use of panel data regression analysis in this research. The results of the study indicate that the allowance for impairment losses contributes considerably to the enhancement of firm value. There is a positive correlation between the values of the business and the quantity of CKPN that is allocated by the corporation. It is quite probable that the value of the company will improve in conjunction with an increase in CKPN. This is because substantial provisions for impairment losses have been set in order to meet any future impairments. It is possible that this will contribute to an increase in investor trust in the firm, indicating that it has positive growth prospects.